The protein kinases family in fungi: adaptability, virulence and conservation between species - La Santrer, Emanoelle; Assunção, Cláudia Barbosa; de Camargo, Thiago Miguelito Navarro; Rodrigues, Izabella; Campolina, Sabrina Sidney; de Aguiar, Edgar Lacerda; de Souza Rodrigues, Thiago; Caligiorne, Rachel Basques (Frontiers in Microbiology, 2025)
Protein Kinases (PKs) are a large family of enzymes that act as “molecular switches,” playing fundamental role in cellular signaling through protein phosphorylation. This process consists in transfer a phosphate group (γ-PO₄2−) from ATP (adenosine triphosphate) to specific residues in target proteins; thereby, controlling vital cellular processes, such as (i) cell proliferation and differentiation, (ii) response to environmental stimuli (stress, nutrients, hormones), (iii) metabolism, (iv) cell cycle and apoptosis, and (v) signal transduction. Among fungi, adaptability is intrinsically connected to their ability to thrive under extreme environmental stress, being morphological plasticity an example of this adaptability. While many of these adaptive responses are regulated by diverse signaling pathways involving different kinase families, as mitogen-activated protein kinase (MAPK) for example, this review places a special focus on the General Control Nonderepressible 2 kinase (GCN2), a highly conserved sensor of amino acid scarcity in many fungi, as well as the species Cryptococcus neoformans, Candida albicans, and Aspergillus fumigatus. Amino acid deprivation triggers the accumulation of uncharged tRNAs, which directly activate GCN2, and this activation leads to the phosphorylation of the eukaryotic initiation factor 2 alpha (eIF2α) at the serine in the position 51, initiating the Integrated Stress Response (ISR). Phosphorylated eIF2α suppresses global translation initiation while selectively enhancing the translation of stress-responsive genes, notably GCN4, which encodes a transcription factor that promotes amino acid biosynthesis and stress adaptation. In Cryptococcus neoformans, GCN2 emerges as the sole kinase responsible for eIF2α phosphorylation, a unique role in modulating translational responses to environmental and host-induced stressors. Previous studies have shown that the absence of GCN2 disrupts eIF2α phosphorylation, impairing stress responses and reducing pathogenicity, therefore being an important target for development of new generation antifungals. To better understand the mechanistic role of GCN2 and related kinases in amino acid sensing and stress response, we present a review based on studying the central role of kinases in fungal stress adaptation, discussing how the high conservation of their catalytic kinase domains makes them valuable as phylogenetic markers and therapeutic targets.